Print workshop : hand-printing techniques + truly original projects - Schmidt, Christine, 1979- (Potter Craft, 2010)
Demonstrates a range of affordable printing techniques that can be accomplished at home, sharing creative suggestions for everything from wedding invitations and t-shirts to a deck of cards and decorative pillows.